Reorganisasi Partai Keadilan Sejahtera di Indonesia - AMINUDDIN, FAISHAL (Universitas Muhammadiyah Yogyakarta, 2010)
Indonesian politics after New Order drawing the raise of political islam movement. Partai KeadilanSejahtera (PKS) Welfare Justice Party bring a newest ideological looked that rooted from Islamic value.This article tend to explore reorganizing of PKS in important periods. It capture changing the namefrom PK to became PKS which contained switching a fundamental movement typology from dakwahwhich emphasizing social and mass mobilisation to political reorganisation. This article's method isliterature review. This period being critical phase that PKS has successful to maintain theiri ideologyand compromise with political pathways. Indeed, PKS has one of the most influent party in the futureindonesian politics.